(3GdCMhGd GdTNUjI aj GdLQGFe GdeGSI GdJj JgOO MjGI GdCSQI (B:s (3LQjeI JSHjH GdhdO(B-(3JYQjV GdWad ddNWQ(B-(3EgeGd hGLHGJ GdCSQI(B-(3LQjeI bJd GdCe dhdjOgG(B-(3bJd GdCe HSHH JCKjQ GdhdGOI Ch GdQVGYI(B-(3GdLQGFe GdLfSjI GdJj JeS CYQGV GdCSQI(B-(3LQjeI GdGZJUGH GdJj JeS GdCSQI hYbhHJgG(B-(3GdQcf GdeYfhj ddbUO GdLfGFj(B-(3gJc GdYQV HGdNOGY Ch HSHH GdMGdI GdLSOjI Ch GdfaSjI(B-(3LQjeI EaSGO GdQGHWI GdRhLjI(B-(3CQcGf LQjeI GdJYOj Ydi MQGSI GdbGUQ (B: ((3OQGSI ebGQfI(B) /s - (3fhM, dDj YHO Gddgs ((3GdLjRI, LeghQjI eUQ GdYQHjI (B:s (3eQcR GdOQGSGJ GdYQHjI ddfTQ hGdJhRjY,s, 2019)
(3jJfGhd cJGH (B((3GdCMhGd GdTNUjI aj GdLQGFe GdeGSI GdJj JgOO MjGI GdCSQI(B) (3GdPj bGe HJCdjag dDj YHO Gddg fhM aj MhGdj (B(222) (3UaMI ef GdbWY GdeJhSW ehVhY (B((3GdCMhGd GdTNUjI(B) (3eJVefG GdeMJhjGJ GdJGdjI (B: (3LQjeI JSHjH GdhdO, JYQjV GdWad ddNWQ, EgeGd hGLHGJ GdCSQI LQjeI bJd GdCe dhdjOgG, bJd GdCe HSHH JCKjQ GdhdGOI Ch GdQVGYI, GdLQGFe GdLfSjI GdJj JeS CYQGV GdCSQI, LQjeI GdGZJUGH GdJj JeS GdCSQI hYbhHJgG, GdQcf GdeYfhj ddbUO GdLfGFj, gJc GdYQV HGdNOGY Ch HSHH GdMGdI GdLSOjI Ch GdfaSjI, LQjeI EaSGO GdQGHWI GdRhLjI, CQcGf LQjeI GdJYOj Ydj MQGSI GdbGUQ(B.s
(3HHdjhLQGajI (B: (3UaMI (B211-220.s
Keywords: (3GdbGfhf GdLfGFjs -- (3GdHdGO GdYQHjIs; (3LQGFe VO GdCTNGUs -- (3bhGfjf hJTQjYGJs -- (3GdHdGO GdYQHjIs; (3GdCSQIs -- (3bhGfjf hJTQjYGJs -- (3GdHdGO GdYQHjIs; (3GdRhGLs -- (3bhGfjf hJTQjYGJs -- (3GdHdGO GdYQHjIs; (3GdLQGFe GdLfSjIs -- (3bhGfjf hJTQjYGJs -- (3GdHdGO GdYQHjIs; (3GdCSQIs -- (3bhGfjf hJTQjYGJs -- (3GdHdGO GdYQHjIs; (3GdGZJUGHs -- (3bhGfjf hJTQjYGJs -- (3GdHdGO GdYQHjIs; (3GdbUO GdLfGFjs -- (3GdHdGO GdYQHjIs; (3gJc GdYQVs -- (3bhGfjf hJTQjYGJs -- (3GdHdGO GdYQHjIs; (3LQGFe GdCSQIs; (3LQjeI JSHjH GdhdOs; (3LQjeI bJd GdCe dhdjOgGs; (3LQjeI GdGZJUGHs; (3LQjeI gJc GdYQVs; (3GdCgdjI GdbGfhfjI ddRhGLs; (3fSH GdWads; (3MQGSI GdbGUQs; (3GdQcf GdeYfhjs